Characterization of the microenvironment of diabetic foot ulcers and potential drug identification based on scRNA-seq - Li, Yao; Ju, Shuai; Li, Xiaoyan; Li, Wenqiang; Zhou, Siyuan; Wang, Guili; Cai, Yunmin; Dong, Zhihui (Frontiers in Endocrinology, 2023)
Diabetes foot ulcers (DFU) are a type of foot infection, ulcer, and/or deep tissue destruction caused by neuropathy and vascular disease in the distal extremities of diabetic patients. Its pathogenesis is not entirely understood.Initially, the GSE165816 data set from the GEO database was utilized for single cell analysis to reveal the microenvironment and functional status of DFU. The GSE199939 rnaseq data set was utilized for external validation. On the basis of the logistic regression machine learning algorithm, pseudo time series analysis, dryness index analysis, and drug target gene analysis were then performed (OCLR). By constructing drug-gene and gene-gene-gene-drug-gene networks, we can locate the most recent DUF treatments.Finally,qRT-PCR and western blotting(WB) were used to verify the expression of drug targets in DFU.Firstly, human cells and related gene markers were retrieved manually by cell clustering. Forty-five cell clusters were found in the DFU microenvironment and divided into 17 different cell types.The pseudo time series analysis of the cells in DFU revealed that leukocytes, macrophages, and monocytes appeared in the ulcer microenvironment earlier than stromal cells and pluripotent stem cells. The stem cells were then assessed. At the level of a single cell, the scores of both multipotential stem cells and hematopoietic stem cells were significantly lower in DFU healing and non-healing than in DM. Additionally, the highly expressed genes in DFU were chosen as drug targets. We identified seven potential target genes and discovered twenty drugs with high significance.Finally,qRT-PCR showed that the expression levels of ANPEP, BID, CYBA, CYBB, FCER1G, ITGA1 and PLAUR were significantly higher than those of healthy subjects, while WB suggested increased expression levels of macrophage markers CD11b and CD163.This study can serve as a resource for the treatment of DFU.